Adherence to DASH Dietary Pattern Is Inversely Associated with Osteoarthritis in Americans (P18-012-19). (13th June 2019) - Francis, Ellen; Kemper, Karen; Williams, Joel; Chen, Liwei
Abstract: Objectives: Osteoarthritis (OA) is a common disease which significantly contributes to disability among older adults. Dietary factors are suggested to play a role in preventing OA, however, studies in this area spare. The objective of this study was to assess the association between adherence to the Dietary Approaches to Stop Hypertension (DASH) and OA in American adults. Methods: This study included United States (US) adults (≥aged 20 years) who participated NHANES cycles 2007–2016. The Dietary Approaches to Stop Hypertension (DASH) score was calculated from nine food items with a higher DASH score indicating better adherence to the DASH dietary pattern. Multivariable logistic regression models adjusted for age, education, race/ethnicity, household income, smoking, alcohol consumption, and total energy intake were used to estimate the adjusted odds ratios (aOR) and 95% confidence intervals (CI) of DASH with OA. All analyses accounted for the complex survey design. Results: Among the 17, 349 participants included in this study, 9.05% reported OA. The DASH score was inversely associated with OA. The aOR (95% CI) were 1.00 (ref), 0.09 (0.70, 1.16), and 0.74 (0.58, 0.94) ( P trend  = 0.01) across the DASH score tertiles. When analyses were stratified by BMI categories (normal, overweight, obese) the magnitude of the association was stronger and remained significant only among obese participants (i.e., BMI ≥ 30 kg/m 2 ). Among participants with an obese BMI, participants with a DASH score in the highest tertile compared to participants with a DASH score in the lowest tertile had a 17% lower likelihood of having OA ( P  = 0.009). Conclusions: In a representative sample of American adults, higher adherence to the DASH dietary pattern was associated with lower likelihood of having OA and this association was particularly evident among obese individuals. Funding Sources: N/A. Supporting Tables, Images and/or Graphs: